Design and Manufacture of Laminated Veneer Lumber Packaging Boxes and Pallets and Evaluation of Their Mechanical Properties - Rongzhuo Zhang; Yuhang He; Assima Dauletbek; Zhaoyu Shen; Yuhao Zhou; Zheng Wang (BioResources, 2022)
Wooden packaging boxes and pallets are used in a wide range of applications. In this work, LVL from the same source and batch were used as the base material. After dynamic detection and grading, they were divided into two grades (A and B), according to their differences in elastic modulus. The packaging boxes and pallets of the same specifications were designed and manufactured as the research objects. Four mechanical properties studies and related analyses were performed. The three mechanical tests showed different deflection values of the two packaging boxes A and B, and the maximum error was 6.93%. In the rotational edge drop test, the edges of the nether end rails of the two grades of LVL boxes were damaged to varying degrees. Additionally, the nails at the connection between the middle longitudinal beam and the bottom plate also appeared to be pulled out, and the parts made of B-grade LVL were more obvious. The results show that the dynamic detection and quality grading for LVL can effectively distinguish the material grade. The grading results were consistent with the mechanical properties of the LVL packaging boxes and pallets of corresponding grades, which are suitable for use in production lines.